Electronically and Geometrically Modified Single‐Atom Fe Sites by Adjacent Fe Nanoparticles for Enhanced Oxygen Reduction - Zhao, Shu‐Na; Li, Jun‐Kang; Wang, Rui; Cai, Jinmeng; Zang, Shuang‐Quan (Advanced materials (Weinheim), 2022)
Fe–N–C materials exhibit excellent activity and stability for oxygen reduction reaction (ORR), as one of the most promising candidates to replace commercial Pt/C catalysts. However, it is challenging to unravel features of the superior ORR activity originating from Fe–N–C materials. In this work, the electronic and geometric structures of the isolated Fe–N–C sites and their correlations with the ORR performance are investigated by varying the secondary thermal activation temperature of a rationally designed NC‐supported Fe single‐atom catalyst (SAC). The systematic analyses demonstrate the significant role of coordinated atoms of SA and metallic Fe nanoparticles (NPs) in altering the electronic structure of isolated Fe–N–C sites. Meanwhile, strong interaction between isolated Fe–N–C sites and adjacent Fe NPs can change the geometric structure of isolated Fe–N–C sites. Theoretical calculations reveal that optimal regulation of the electronic and geometric structure of isolated Fe–N–C sites by the co‐existence of Fe NPs narrows the energy barriers of the rate‐limiting steps of ORR, resulting in outstanding ORR performance. This work not only provides the fundamental understanding of the underlying structure–activity relationship, but also sheds light on designing efficient Fe–N–C catalysts. The correlations between electronic and geometric structures of isolated Fe–N–C sites and their oxygen reduction reaction (ORR) performance are investigated by varying the secondary heat‐treatment of a NC‐supported Fe single‐atom catalyst. The adjacent Fe nanoparticles can regulate the electronic and geometric structure of isolated Fe–N–C sites, reducing energy barriers of the rate‐limiting steps of ORR, resulting in outstanding ORR performance.